2021
DOI: 10.1364/boe.426366
|View full text |Cite
|
Sign up to set email alerts
|

Centimeter-scale wide-field-of-view laser-scanning photoacoustic microscopy for subcutaneous microvasculature in vivo

Abstract: We developed a simple and compact laser-scanning photoacoustic microscopy (PAM) for imaging large areas of subcutaneous microvasculature in vivo. The reflection-mode PAM not only retains the advantage of high scanning speed for optical scanning, but also offers an imaging field-of-view (FOV) up to 20 × 20 mm2, which is the largest FOV available in laser-scanning models so far. The lateral resolution of the PAM system was measured to be 17.5 µm. Image experiments on subcutaneous microvasculature in in vivo mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The use of a double-sided illumination in depth and roving scans in the transverse plane extended the spatial FOVs to 30 mm (axial) toward phantoms and 9.5 cm × 9.5 cm (lateral), which are at least tenfold larger than that of conventional PAMs. [25][26][27] The decellularization for organ transparency permits a comprehensive assessment of the vessel systems over entire organs with PAM approaches, making it accessible for large animal and even human organs in the clinical setting. In addition, utilization of the photoacoustic gradient concentration differential angiography fully contrasts the multiscale vascular networks and extensively simplify the segmentation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a double-sided illumination in depth and roving scans in the transverse plane extended the spatial FOVs to 30 mm (axial) toward phantoms and 9.5 cm × 9.5 cm (lateral), which are at least tenfold larger than that of conventional PAMs. [25][26][27] The decellularization for organ transparency permits a comprehensive assessment of the vessel systems over entire organs with PAM approaches, making it accessible for large animal and even human organs in the clinical setting. In addition, utilization of the photoacoustic gradient concentration differential angiography fully contrasts the multiscale vascular networks and extensively simplify the segmentation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TUTs based on the piezoelectric active element in particular have gained significant interest from multiple groups in the photoacoustic and ultrasound community due to their versatility and cost effectiveness 170–176 . For example, Chen et al 177 used LiNbO3‐based TUT to image chicken embryo vasculature and for melanoma detection.…”
Section: Current Challenges and Future Trendsmentioning
confidence: 99%
“…Reprinted with permission 148 versatility and cost effectiveness. [170][171][172][173][174][175][176] For example, Chen et al thinned-skull window. 179,180 The TUT cranial window allowed us to use three different modalities OR-PAM, TPM, and IOSI to image awake mouse brain vasculature using a head restraint setup.…”
Section: Current Challeng E S and Future Trendsmentioning
confidence: 99%
“…This will not only significantly reduce the beam engineering challenges but will also lead to the development of a more compact, portable, wearable, and versatile multimodal systems. For this purpose, both conventional piezoelectric materials [40][41][42][43] and capacitive micromachined ultrasound transducers (CMUTs) [44][45][46] have been studied for developing TUTs. Ilkhechi et al reported transparent CMUT array for ultrasound imaging of a small size tissue phantom [45] and photoacoustic [46] imaging of pencil leads submerged in oil tank.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these detectors cannot be used for ultrasound excitation/imaging required for dual-modality USPA imaging applications. While prior studies demonstrated the potential of transparent lithium niobate-(LN-) based single element TUTs for high sensitivity PA imaging [40][41][42][43], TUT-arrays are required for real-time multimodal imaging.…”
Section: Introductionmentioning
confidence: 99%